2005
DOI: 10.1111/j.1365-2249.2005.02898.x
|View full text |Cite
|
Sign up to set email alerts
|

Defining the role of T cell-derived leptin in the modulation of hepatic or intestinal inflammation in mice

Abstract: The role of leptin in the immune system has been well established. While adipocytes represent the major source, leptin production by lymphocytes, infiltrating at the site of inflammation, was recently demonstrated. However, the significance of this locally released leptin remains unresolved. In the present study, two models in which absence of leptin-signalling is associated with protection were employed: the model of ConA-induced hepatitis and the CD4(+)CD45Rb(high) transfer model of colitis. For the ConA mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 35 publications
(52 reference statements)
2
33
1
Order By: Relevance
“…Among these factors, only leptin and adiponectin (and possibly resistin, adipsin and visfatin) are primarily produced by adipocytes, and they can therefore be properly classified as adipokines. 10 In particular, leptin is considered the prototypical adipokine.…”
Section: Introductionmentioning
confidence: 99%
“…Among these factors, only leptin and adiponectin (and possibly resistin, adipsin and visfatin) are primarily produced by adipocytes, and they can therefore be properly classified as adipokines. 10 In particular, leptin is considered the prototypical adipokine.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the name 'eosinophilic', EGCs may have different staining affinities, basophilic or eosinophilic, depending on the species considered and the conditions of fixation (Rocha & Chiarini-Garcia 2007). The involvement of leptin in inflammation is well-established in birds and mammals (Lõhmus et al 2004;Matarese et al 2005); in particular, it has been demonstrated that, in the mammalian intestine, lymphocytes release leptin at the inflammation site (Siegmund et al 2004;Fantuzzi et al 2005). Our data therefore suggest that leptin can be involved in immune and inflammatory responses in teleosts, in addition to its better-known role as a regulator of energy homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…Mast cells also express leptin and leptin receptors, a finding implicating paracrine or autocrine immunomodulatory effects of leptin on mast cells (Taildeman et al, 2009). Locally released leptin from T lymphocytes doesn't seem to play a major role in immunoregulation in mouse models of intestinal inflammation, suggesting other sources of leptin as critical in modulation of the inflammatory response (Fantuzzi et al, 2005). Despite evidence supporting the role of leptin in immune processes (Lago et al, 2008;Matarese et al, 2005), its precise role in inflammation remains incompletely understood.…”
Section: Other Perinatal Risk Factorsmentioning
confidence: 99%